PCR- and ligation-mediated synthesis of marker cassettes with long flanking homology regions for gene disruption in Saccharomyces cerevisiae. - Nikawa, J (1998)
We developed a novel method for synthesizing marker-disrupted alleles of yeast genes. The first step is PCR amplification of two sequences located upstream and downstream of the reading frame to be disrupted. Due to the addition of non-specific single A overhangs by Taq DNA polymerase, each PCR product can be ligated with a marker DNA which has T residues at its 3' ends. After amplification of individual ligation products through the second PCR, both products are mixed and annealed, and the single strand is converted to a double strand by an extension reaction. The final step is PCR amplification of the fragment composed of a selectable marker and two flanking sequences with the outermost primers. This method is rapid and needs only short oligonucleotides as primers.